(untitled) (Research, Society and Development, 2021)
The present study aimed to analyze the morphometry of fruits, seeds and seedlings of Guazuma ulmifolia Lam., In addition to testing different treatment modalities to overcome the dormancy of its seeds. Initially, the biometry of fruits and seeds and, later, seedlings were performed. The treatments used for breaking dormancy were: control (T1); chemical scarification with sulfuric acid (H2SO4) 98% for 5 min (T2), 15 min (T3), 30 min (T4) and 50 min (T5); chemical scarification with sulfonic acid (H-S (= O) 2-OH) for 50 min (T6) and 60 min (T7); chemical scarification with muriatic acid (HCl) for 60 min (T8) and; immersion in hot water (T9) at 90 ° C for 10 min. After undergoing the treatments, the seeds were sown on sheets of germitest paper. The germination percentage (% G), the germination speed index (IVE) and the average germination time (TME) were evaluated. The experimental design used was entirely random. The data were subjected to analysis of variance and the comparison between the averages performed using the Tukey test at 5% significance. Only the immersion treatment in hot water at 90º C for 10 min was efficient to overcome dormancy in G. ulmifolia seeds, providing 68% germination. The other treatments did not significantly increase germination, being equal to the control. For the analysis of variance of the TME, it was observed that there was no significant difference in any of the treatments.